Problems and prospects of competency-based approach in pedagogy of high school - Nabiev V. S. (Pedagogics and psychology: relevant theoretical and practical questions, 2016)
deals with topical issues of organizing the activity of subjects of a holistic educational process in the conditions of transition to competency format of diagnosing, monitoring and evaluating results and achievements of students
Keywords: компетентностный подход; образовательный процесс; достижения; результаты; educational process; achievements; Competence approach; results; характеристики целостности; признаки соответствия; the holistic characteristics; traits of relevance